EUFEMISME SEBAGAI TINDAK KOMUNIKASI YANG BERADAB DALAM BAHASA JAWA - Dwi Sutana (Madah: Jurnal Bahasa dan Sastra, 2012)
Behavior has a close relationship with language. The expression of courtesy and spoken word always refer to behavior, manner and morality, etc. Hence, behavior reflects in speaking actions. As cultured and civilized being, it is necessary to choos e words based on ethics, courteous and good objective in communication. In  relation with the speaking actions, a certain way could be applied  by using euphemism. Euphemism is such kind of reference of subtle expressions in order to replace the references that may be felt as offensive, insulting and suggesting something unpleasant. The problem in this research is focused on to what fields are the euphemism used in Javanese. This article applied Verhaars theory specifically about the meaning concept, inten tion, and information. Based on the research, it showed that euphemism is uttered in order to soften the speech so that others will not be bothered or emotional which can cause anger, impoliteness and offending so there would be the thoughtful behavior.